Efektivitas Pemanfaatan Serbuk Gergaji dan Limbah Media Tanam Jamur (Baglog) sebagai Bahan Baku Pembuatan Biogas - Dikdik Mulyadi; Lela Mukmilah Yuningsih; Desi Kusumawati (Jurnal Kimia Valensi, 2016)
Biogas is  one of energy   that can be produced by anaerobic fermentation of the organic compounds. The objective of this study was to determine the effectiveness of the utilization of waste of media  mushroom growth (baglog) with sawdust as raw material for biogas with  cow dung  activators. The study was conducted through anaerobic fermentation of the samples containing waste baglog (sample 1) and sawdust (sample 2), with the addition of cow manure activator to each sample. Both of these samples do anaerobic fermentation for 32 days, then measuring the volume of biogas every 4 days for 32 days. Methane content  in  samples 1 and 2 measured by  using gas chromatography. To see the effect of the addition of activators cow dung biogas volume measurement was  carried out with  cow dung without addition baglog waste and sawdust. The process of degradation baglog and sawdust with an activator of cow dung could be observed  in  some of the parameters through  total solids (TS), total volatile solids (TVS), volatile fatty acids (VFA), the degree of acidity (pH), and C/N ratio. The results showed that effectiveness of sample 1 resulted in the everage of total volume biogas 28% higher than  sample 2. The content of methane in  sample 1  and sampel 2  was 54% %, and 0.21% respectively. The fermentation process biogas production in this experiment  was carried out  at pH 7, with a value of TS, TVS and VFA showed a decrease  trend after the fermentation process,  C/N ratiowas  lower than the baglog waste sawdust until day 32 retention time. Keywords: Sawdust, baglog waste, biogas, fermentation, methane DOI : http://dx.doi.org/10.15408/jkv.v2i1.3100